A content analysis on race in drama therapy empirical research. Issue 1 (1st April 2023) - Lee, Erica Laikah; Morris, Mary Elizabeth; Rowe, Chyela; Moreno, Michelle; Navarro, Jonathan
Drama therapy empirical research has the potential to support growth within the profession, but changes are still needed to address a lack of racially diverse perspectives represented in studies. A Black, Indigenous and People of Color (BIPOC) research sub-committee of the North American Drama Therapy Association (NADTA) was formed and members took on the task of reading full-text available articles listed in the NADTA empirical references list ( N = 123) with the aim of identifying representations of race within the research through a content analysis. Our team found limited examples of both author-identified race information and contextualized participant racial demographics. When race was presented, most often as descriptive statistics alone, contextual information about culture or other relevant supportive literature was often lacking. Further research and a more systematic critical review of existing drama therapy empirical studies are needed to formulate recommendations for addressing racial disparities within drama therapy research.